Development of Reaction-Rectification Process of Obtaining Mesityl Oxide. II. Analysis of Statics and Modeling of the Process - M. A. Yakhyaev; V. S. Gutenkov; C. A. Cardona; Yu. A. Pisarenko (Тонкие химические технологии)
Using the results of an earlier study of the physicochemical properties of the reaction system of the process of producing mesityl oxide, an analysis of the statics of the combined variant of the organization of this process was carried out. It is shown that of practical interest are the modes of the process corresponding to the first specified separation. In this case, the limiting stationary states, characterized by the maximum acetone conversion, selectivity, and the yield of the target product — mesityl oxide, are distinguished. The possibility of practical implementation of the limiting stationary state of the reactive distillation process for producing mesityl oxide, which provides almost complete conversion of acetone with a yield of mesityl oxide approaching 100%, has been proved. The limit stationary state corresponds to the reaction-distillation process with the selection of a single product stream. For the mode of carrying out the combined process that corresponds to the selected limiting stationary state, a schematic flow chart for the production of the target product has been proposed. By means of computational research, it has been established that the most rational option for organizing a reaction hub is to use a single apparatus in it — the reaction-distillation column. In the Aspen Plus® software package, a process model was constructed that corresponded to the proposed technological scheme and through a computational experiment, its structural and parametric optimization was carried out. As a result, the static parameters of the technological system were established, as well as the characteristics of the apparatuses, allowing to obtain the required quality product in the reactiondistillation column. output, approaching 100%. It has been shown that when modeling a chemicaltechnological system, it is necessary to use different sets of parameters of the basic equation used to describe phase equilibrium. Thus, for calculating reactive distillation and distillation columns, the liquid – vapor phase equilibrium parameters for the mesityl oxide–water system should be used, and when calculating the Florentine vessel for this mixture, it is necessary to use the parameters corresponding to the liquid – liquid equilibrium. The use of a single set of parameters of the basic equation leads to significant errors and inadequate description of the process of producing mesityl oxide by condensation of acetone.